Suitability of using the torsional amplification factor to amplify accidental torsion. (15th November 2016) - Lin, Jui-Liang; Wang, Wei-Chun; Tsai, Keh-Chyuan
Highlights: Discrepancy curves of accidental torsion effects are constructed. Discrepancy curves of estimated elastic displacements are constructed. The trends in the investigated discrepancies are highlighted. Suggestions on the torsional amplification factor are made. Abstract: The accidental torsion effect on the seismic responses of a building is considered by adding the accidental eccentricity to the existing eccentricity. While buildings are torsionally irregular, the static analysis approach stipulated in some building codes further multiplies the accidental eccentricity by the torsional amplification factor Ax to account for the possible increase of the accidental torsion. This study applies the discrepancy curves to investigate the suitability of using the torsional amplification factor to amplify accidental torsion. The discrepancy curves show the exceedance probabilities of the difference between the responses obtained from static and dynamic analysis approaches. The discrepancy curves of the accidental torsion effects and the estimated elastic displacements were constructed for 3-story, 9-story, and 20-story buildings. Besides the building height, the investigated buildings vary based on four frequency ratios: 0.7, 1.0, 1.3, and 1.6. The existing eccentricity ratios of the investigated buildings range from 0% to 30%. This study also suggests modifications to Ax for estimating the stiff-side displacements of low-rise and medium-rise buildings, while they are torsionally flexible and torsionally similarly stiff.